Nomenclatural changes allow for a broadened circumscription of Lophogyne Tul. to reflect a prominent neotropical clade of Podostemaceae (Podostemoideae) - Philbrick, C. Thomas; Bove, Claudia P. (Phytotaxa, 2019)
Phylogenetic analyses of neotropical Podostemaceae have identified a strongly supported clade comprised of species representing five genera, three of which are exclusive to the clade (Jenmaniella, Lophogyne, Monostylis).  The two other genera (Apinagia, Marathrum) are polyphyletic, with only a subset of species in the clade.  The clade has not been recognized taxonomically.  Herein a combination of four morphological characters are identified that define the clade: at anthesis the ovary is oriented vertically or obliquely and the flower projects from the ruptured spathella, stamens and tepals occur on only one side of the ovary, and silica bodies are absent from the leaves.  Nomenclatural changes are made to transfer all species inclusive to the clade to the genus Lophogyne, which has priority.  The broadened circumscription of Lophogyne (i.e., Lophogyne s.l.) is an important element of the developing classification of neotropical Podostemaceae that reflects phylogenetic understanding.